2013
DOI: 10.1177/0218492313501509
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative predictors of midterm survival after aortic valve replacement

Abstract: 5-year survival among octogenarians was 59.2% with an observed 30-day mortality of 1% for aortic valve replacement and 3% for aortic valve replacement with coronary artery bypass. Kaplan-Meier survival analysis showed that age ≥80 years, New York Heart Association functional class III/IV, and left ventricular ejection fraction <35% were significantly associated with increased midterm mortality. Cox regression modeling demonstrated that age ≥80 years was the only significant independent factor associated with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Seven studies reported data on re-thoracotomy for postoperative bleeding [ 3 , 4 , 6 , 15–17 , 20 , 23 ]. The OR did not reveal significant difference between the 2 groups (OR = 0.84; 95% CI = 0.57–1.23; P = 0.37) with no relevant heterogeneity ( I 2 = 21%; Supplementary Material, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies reported data on re-thoracotomy for postoperative bleeding [ 3 , 4 , 6 , 15–17 , 20 , 23 ]. The OR did not reveal significant difference between the 2 groups (OR = 0.84; 95% CI = 0.57–1.23; P = 0.37) with no relevant heterogeneity ( I 2 = 21%; Supplementary Material, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While in-hospital mortality is increased by the concomitant CABG surgery, as recognized by EuroSCORE and Society of Thoracic Surgeon score, the impact on long-term outcomes is debated. Some studies have reported acceptable and comparable long-term results in those patients who received either i-SAVR or CABG combined with SAVR [ 2 , 3 ], whereas other authors have reported conflicting outcomes, with some studies showing better long-term survival in i-SAVR patients [ 4 ] while others reporting longer-term benefit in CABG+SAVR patients [ 5 , 6 ]. To the best of our knowledge, no randomized control trials or meta-analyses related to the impact on long-term of CABG added to SAVR in octogenarians are available.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 2046 titles and abstracts were identified, of which 57 were considered potentially relevant and for the meta-analysis and retrieved as full-text. After evaluating the full-text articles, 44 studies [ 5 21 , 27 – 53 ] fulfilled the eligibility criteria and were included in the final analysis. All included studies were observational and retrospective in design, an no randomized clinical trials or prospective studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies [ 5 , 7 , 9 , 11 , 13 , 17 21 , 27 , 29 , 34 , 38 , 39 , 41 , 45 , 50 53 ] reported long-term survival comparison between the two surgical interventions with a mean follow-up ranging from 2.1 years [ 27 ] to 9.5 years [ 45 ]. The weighted mean follow-up was 3.2 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation